Unusual association of multiple congenital left ventricular diverticulum and cerebrovascular events in an adult - Mustafa Beyazıt Alkan; Murat Bilgin; Burcu Zihni; Sanem Nalbantgil (KARE Publishing, 2015)
Congenital ventricular diverticulum is a rare and usually asymptomatic cardiac malformation which can cause major complications such as systemic thromboembolism, infective endocarditis, cardiac rupture, heart failure, arrhythmia and sudden death. We present a case with multiple congenital left ventricular diverticulum admitted to hospital with sudden onset right-sided hemiplegia and dysarthria.